ON SOME PROBLEMS OF DISSERTATION OPPONENCY - V. Ya. Gelman (Russian State Vocational Pedagogical University, 2018)
Introduction. Currently, there is a restructuring of the system of training scientific and scientific-pedagogical personnel of the highest qualification. A number of the top-ranking universities and research institutes are given the right to award their own academic degrees. However, the overwhelming majority of dissertational councils (about 2000) continue to work under the guidance and in accordance with the regulatory documents of the Higher Attestation Commission. Therefore, the improvement of the existing system is still relevant.The aims of this article are the following: to consider the main problems and trends emerging in the process of opposing dissertations; to find out the difficulties and their causes; to define possible ways to reduce current problems.Methodology and research methods. The methods involve: analysis of normative documents and scientific publications; methods of expert assessments, self-reflection and synthesis of personal experience of the author.Results and scientific novelty. The main objectives and the existing drawbacks of the work of official opponents are identified. The following questions that arise when opposing dissertations are discussed: the choice and appointment of official opponents by the Dissertation Council, the specifics of the opponents' performance in the defense process and the payment for their work. It is noted that increasing requirements for opposing dissertations and opponents themselves, increasing the responsibility of opponents leads to additional difficulties in their work, in particular, the increase in labour costs that are not adequately compensated. It is concluded that many problems in opposing dissertations are objective in nature and cannot be overcome only by the forces of the opponent himself. Possible ways of solving the detected problems are indicated. Accordingly, along with increasing requirements and responsibilities in regulatory documents, a complex of the organizational and technological measures should be provided to facilitate the work of the opponent, his additional stimulation, including the financial one.Practical significance. The author believes that the approaches and recommendations proposed in this article will help to increase the effectiveness of the opponents' work and, accordingly, assessment system enhancement of the research consistency and academic degrees awarding.